The Dilemma of Copyright in Sub-Saharan Africa: Ghana in Focus - Owusu Sarpong, Eva (Université d'Ottawa | University of Ottawa, 2013)
A just, fair and equitable international copyright system is vital for the proper functioning of knowledge development and access. Thus copyright law has come to occupy the centre stage of international economic development and countries identify it as a powerful catalyst in fostering national economic growth. The terms of international copyright treaties, however, hamper the ability of sub-Saharan Africans to compete effectively with other countries. This research employs a single case study qualitative research design to examine Ghana’s national copyright statutes and the influence on them of its international copyright agreements. Using Rawls’ theory of justice as the conceptual framework for the analysis, this study argues that in spite of the efforts to ameliorate the equity of international copyright systems for developing countries such as Ghana, key features of those systems remain inherently unjust.